A Strategic Tool for Managing Intellectual Capital of Pakistan (The Pakistan Development Review, 2011)
In the post-industrial world, the Intellectual Capital (IC) of nations has become critical for wealth and value creation. In this era of knowledge-based economy, one real challenge that a nation faces is maintenance of its economic growth and its competitiveness in the international market. Policy-makers presently need to have a strategic management tool to measure and develop IC assets of a country. The paper extends the framework of Skandia Navigator [Edvinsson and Malone (1997)] from the corporate to the national level and develops a tool on the extended framework to visualise the intellectual capital of Pakistan. The Intellectual Capital of a country is indirectly visualised through various indices. These indices change from year to year, not necessarily in a consistent manner, so that having a general view would be baffling. To overcome this limitation, this paper proposes three methods of measuring the change in IC based on Financial Index (FI), Human Index (HI), Process Index (PI), Market Index (MI) and Research Index (RI). These tools produce composite IC indices for Pakistan (2005-2010) that can be useful for the development of national policies. Keywords: Intellectual Capital Measurement, Knowledge Management, Strategic Management, Pakistan Economy